2020
DOI: 10.1002/chem.202001346
|View full text |Cite
|
Sign up to set email alerts
|

Degeneracy of the Antithrombin Binding Sequence in Heparin: 2‐O‐Sulfated Iduronic Acid Can Replace the Critical Glucuronic Acid

Abstract: Heparin binds to and activates antithrombin (AT) through a specific pentasaccharide sequence, in which a trisaccharide subsite, containing glucuronic acid (GlcA), has been considered as the initiator in the recognition of the polysaccharide by the protein. Recently it was suggested that sulfated iduronic acid (IdoA2S) could replace this “canonical” GlcA. Indeed, a heparin octasaccharidic sequence obtained by chemoenzymatic synthesis, in which GlcA is replaced with IdoA2S, has been found to similarly bind to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…In the three heparins ( Tables 7 – 9 ), ΔIIs- Is id and ΔIs- Is id were major fragments containing - Is id and their presence, detected essentially in the affinity fractions, was a strong argument for their ATIII binding contribution within a non-conventional pentasaccharide where a 2- O -sulfated iduronic acid is substituted for the canonical central glucuronic acid. These data, compatible with an ATIII binding capacity of sequences including ΔIIs- Is id and ΔIs- Is id , are in line with those recently published ( 5 , 6 ). Table 7 also shows that even in the fraction HA5, the phenomenon of double 3S ATIII pentasaccharides was limited for PMH (5–10% of ΔIIa- IVs glu , and ΔIIa- IIs glu is in ΔIIa- IVs glu - Is id , ΔIIa- IIs glu - Is id sequences) in connection with the low content of Δ Is .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In the three heparins ( Tables 7 – 9 ), ΔIIs- Is id and ΔIs- Is id were major fragments containing - Is id and their presence, detected essentially in the affinity fractions, was a strong argument for their ATIII binding contribution within a non-conventional pentasaccharide where a 2- O -sulfated iduronic acid is substituted for the canonical central glucuronic acid. These data, compatible with an ATIII binding capacity of sequences including ΔIIs- Is id and ΔIs- Is id , are in line with those recently published ( 5 , 6 ). Table 7 also shows that even in the fraction HA5, the phenomenon of double 3S ATIII pentasaccharides was limited for PMH (5–10% of ΔIIa- IVs glu , and ΔIIa- IIs glu is in ΔIIa- IVs glu - Is id , ΔIIa- IIs glu - Is id sequences) in connection with the low content of Δ Is .…”
Section: Resultssupporting
confidence: 93%
“…For the first two disaccharides, Δ Is and Δ IIIs , incompatibility with the structural requirements of the antithrombin III (ATIII) binding sequence suggested that they did not participate in anticoagulant activity and could be classified as non-ATIII-binding units ( 4 ). However, recent studies based on biosynthetic sequences ( 5 , 6 ), showed that the medium glucuronic acid in the pentasaccharide is not mandatory to bind ATIII and could be replaced by a 2- O -sulfated iduronic acid in synthetic octasaccharides, which still have anticoagulant activity. Δ Is and Δ IIIs could then be digested from ATIII binding sequences where their uronic acid is iduronic 2- O -sulfate [-IdoA(2S)-GlcN(NS,3S,6S) and -IdoA(2S)-GlcN(NS,3S)].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the flexibility of IdoA provided unlimited possibilities for the binding of heparin to protein. A recent study used IdoA2S instead of GlcA in the AT III binding sequence (Elli et al, 2020). The results showed that IdoA2S, which replaced GlcA, was in a pure 1 C 4 conformation when bound, and the affinity was tripled, which provided a basis for the application of bovine heparin.…”
Section: Heparin/heparan Sulfatementioning
confidence: 99%
“…The specific pentasaccharide sequence binds and potentiates the effect of antithrombin a naturally occurring anticoagulant, which can inhibit several serine proteases of the coagulation system, primarily FIIa (thrombin) and FXa. More recently, a heparin octasaccharidic sequence obtained by chemoenzymatic synthesis, in which glucuronic acid is replaced with sulfated iduronic acid, was shown to similarly bind to and activate antithrombin, thus paving the way for the development of heparin-like drugs that be obtained by a chemo-enzymatic approach ( Elli et al., 2020 ).…”
Section: Efficacy Of Heparin In Counteracting the Entry Of Sars-cov-2mentioning
confidence: 99%